Benefit of synbiotic intervention in Caesarean section born infants and children: A nutritional perspective - Saptawati Bardosono; Dian Novita Chandra (Indonesian Nutrition Association, 2020)
The benefit to have infants being delivered physiologically through vagina is amongst others to get maternal microbes transmission that will affect host immunity and metabolic development. However this mode of delivery is not always the choice to infants for several reasons. Therefore, it raises questions whether there is a need to give specific intervention to the caesarean section (C-section) born infants and children for their optimal growth and development, i.e. provision of nutrients with or without pre-, pro- or synbiotics. Nutritional intervention is certainly important to support growth and development of all children, especially those born by C-section. However, in addition, to anticipate perturbation in the gut microbiota there is a need to prepare the C-section born infant through translocation from the mother’s intestinal microbiota, early initiation of breastfeeding and/or synbiotic supplementation formula. The superiority of synbiotic compare to prebiotic or probiotic alone is that synbiotic thought to have synergistic beneficial effects on the immune and metabolic systems in which it compensates the delayed Bifidobacterium colonization in C-section delivered infants and modulates the production of acetate and the acidification of the gut. However we still need to find consistent evidence & recommendation in the world on synbiotic for children in general and specifically for the C-section born infant & children that may have an impact on healthy young children’s gut microbiota.